A Multifaceted Investigation of Factors Contributing to General Fatigue in Hot Work Environments - Shahram Vosoughi; Ensieh Sadat Alamshah; Jamileh Abolghasemi Talkhooncheh; Somaye Taqizade (بهداشت و ایمنی کار)
Introduction: Heat stress is a common environmental risk factor for many occupations, which can lead to increased fatigue during cognitive tasks. Fatigue is a multifactorial phenomenon that is affected by various environmental, physiological, and psychological factors, and can affect biomechanical, physiological, and psychological components. This study focuses on the impact of environmental, individual, and physiological factors, and burnout on general fatigue. Material and Methods: This descriptive-analytical study was conducted among 189 employees of the Iran Oil Company at both indoor and outdoor workstations. Heat stress was measured using the (WBGT) index, and thermal strain risk was evaluated. Variables such as skin temperature, ear temperature, blood pressure, and heart rate were also monitored. To assess general fatigue and occupational burnout, (MFI) and the Maslach Burnout Inventory were completed by the employees. Results: The results revealed that 79.9% of the employees were exposed to heat stress, with repair workers experiencing the highest levels of emotional exhaustion (23/38), depersonalization (15/34), general fatigue (10/00), and physical fatigue (9/05).  Statistically significant relationships were found between heat stress and fatigue and decreased motivation, between all components of burnout and general fatigue, and between core temperature, blood pressure, and general fatigue (p<0.05). Notably, demographic factors such as marital status, smoking status, and education level did not significantly influence fatigue scores. Conclusion: Fatigue is strongly associated with heat stress, physiological variables such as body temperature and blood pressure, burnout, personal habits such as sleep duration and exercise, and the type of job. These findings suggest that in hot work environments, monitoring physiological variables and environmental factors can help identify and address fatigue issues.